LE RÔLE SOCIAL DU JUGE - DAN, Roxana (Studia Universitatis Babeș-Bolyai Philosophia, 2017)
The Social Role of the Judge. One primary task that a judge has in the process of his activity is to interpret the law according to every single given case. The meaning of the present research is to enlighten the limits that a judge has in the process of interpretation, in particular regarding the question if the law can be construed according to the social context contemporary with the judge. Is this a desirable way of interpreting the law, in compliance with a democratic system or it interferes with the principle of the separation of powers?